2003
DOI: 10.1021/bp0201298
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Catalyzed Synthesis of Butyl Butyrate by Alcoholysis in an Integrated Liquid-Vapor System

Abstract: This paper reports experimental work pertaining to alcoholysis between butanol and ethyl butanoate, catalyzed by an immobilized lipase in a liquid-vapor system where chemical reaction and physical separation are simultaneously carried out. The processing setup was tested for various compositions of the starting feedstock and operated under reduced pressure. Samples were withdrawn both from the boiler and the condenser, and they were chromatographically assayed for butyl butyrate. The integrated configuration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…Lipases (triacyl glycerol hydrolases, E.C. 3.1.1.3) are used to breakdown fats, triglycerides, and can be used for esterification and transesterification in organic solvents,3–20 in supercritical fluids21–31 and solvent free condition 32–34. Lipase are more stable at higher pressures,35 some studies have shown surfactant‐coated lipase,3 lipase encapsulated in silica aerogels4, 5 and lipase encapsulated in microemulsion‐based organogels give better activity and, therefore, can be used more effectively for esterification and transesterification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipases (triacyl glycerol hydrolases, E.C. 3.1.1.3) are used to breakdown fats, triglycerides, and can be used for esterification and transesterification in organic solvents,3–20 in supercritical fluids21–31 and solvent free condition 32–34. Lipase are more stable at higher pressures,35 some studies have shown surfactant‐coated lipase,3 lipase encapsulated in silica aerogels4, 5 and lipase encapsulated in microemulsion‐based organogels give better activity and, therefore, can be used more effectively for esterification and transesterification.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of esterification to butyl isobutyrate6 was reported in heptane ignoring the kinetics of hydrolysis. Some studies have reported the integrated liquid–vapor32 and solid–liquid–vapor33 system for synthesis. Santos et al 7 used factorial design to optimize the lipase catalyzed synthesis of butyl butyrate in heptane, while Lozano et al 9 studied the continuous synthesis of butyl butyrate using an active membrane coated with lipase.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of esterification to butyl isobutyrate 6 was reported in heptane ignoring the kinetics of hydrolysis. Some studies have reported the integrated liquid-vapor 32 and solid-liquid-vapor 33 system for synthesis. Santos et al 7 used factorial design to optimize the lipase catalyzed synthesis of butyl butyrate in heptane, while Lozano et al 9 studied the continuous synthesis of butyl butyrate using an active membrane coated with lipase.…”
Section: Introductionmentioning
confidence: 99%
“…Further advantages such as overcoming equilibrium limitations, achieving higher selectivity, reducing catalyst requirement, easier separation of azeotropic mixtures, avoidance of hot spot or use of reaction heat for the distillation have resulted in significant interest in RD as an alternative process for the chemical industry and academia, in recent years [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%